Reimagining Catfish (Clarias sp.) Cultivation: Crafting Sustainable Feed for Economic Prosperity and Eco-Friendly Practices in Simple Concrete Ponds - Budiyanto, Didik; Hendarto, Totok; Sutarmin, Sutarmin; Ardianik, Ardianik (CV. Bimbingan Belajar Assyfa, 2025)
Catfish cultivation in Indonesia is crucial for food security and the economy, but faces efficiency and sustainability challenges. This study analyzes the impact of feed quality on production efficiency, economics, and environmental sustainability in simple concrete ponds. Using a controlled experimental design and three different feed treatments, results show that high-quality feed reduces the Feed Conversion Ratio (FCR), increases biomass, and provides better economic returns. Eco-friendly feed also supports water quality stability. These findings highlight the importance of feed innovation for sustainable aquaculture and recommend cross-sector collaboration to strengthen food systems.